Analysis of thermal expansivity of solids at extreme compression - Shanker, J.; Singh, B.P.; Jitendra, K. (Condensed Matter Physics, 2008)
Thermodynamics of solids in the limit of infinite pressure formulated by Stacey reveals that the thermal expansivity
(alpha) of solids tends to zero at infinite pressure. The earlier models for the volume dependence
of thermal expansivity do not satisfy the infinite pressure behaviour of thermal expansivity. The expressions
for the volume dependence of the isothermal Anderson- Gruneisen parameter (delta T) considered in the
derivation of earlier formulations for alpha (V) have been found to be inadequate. A formulation for the volume
dependence of delta T is presented here which is similar to the model due to Burakovsky and Preston for the
volume dependence of the Gruneisen parameter. The new formulation for alpha (V) reveals that delta T infinity
must be greater than zero for satisfying the thermodynamic result according to which alpha tends to zero at
in nite pressure. It is found that our model fits well the experimental data on thermal expansivity alpha (V) for
hcp iron corresponding to a wide range of pressures (0 360 GPa). Згiдно умови, сформульованої Стейсi для термодинамiки твердих тiл в границi нескiнченого тиску, їх термiчне розширення прямує до нуля при нескiнченому тиску. Попереднi моделi для опису залежностi термiчного розширення вiд об’єму не задовiльняють цiй умовi. Вирази для залежностi iзотермiчного параметра Андерсона-Грюнайзена вiд об’єму, отриманi в попререднiх формулюваннях, виявилися невiдповiдними. Нами представлено об’ємну залежнiсть параметра Андерсона-Грюнайзена, яка є подiбною до отриманої ранiше для однiє з моделей. Отриманi нами результати демонструють, що параметр Андерсона-Грюнайзена при нескiнченому тиску мусить бути бiльшим нiж нуль для того, щоб задовiльнити термодинамiчну умову, згiдно якої термiчне розширення прямує до нуля при нескiнченому тиску. Знайдено, що наша модель узгоджується добре з експериментальними даними, що стосуються об’ємної залежностi для залiза з гексагональною щiльною упаковкою в широкiй
областi тискiв (0–360 GPa).